Cyclization and oxidation of o-bromophenylacetamides for the synthesis of oxindoles and isoindigoes. Issue 2 (11th January 2018) - Liu, Liang; Song, Lei; Guo, Yujun; Min, Dewen; Shi, Tianchao; Zhang, Wu
Abstract: N -substituted oxindoles were obtained through a facile KOH/DMSO promoted intramolecular cyclization of o -bromophenylacetamides in good yields. Furthermore, isoindigo derivatives were readily synthesized through sequential intramolecular cyclization, oxidation and condensation of o -bromophenylacetamide in the presence of copper (II) acetate monohydrate, iodobenzene diacetate and KOH/DMSO. This method provides a convenient synthesis of a range of oxindoles and symmetrical biologically important ( E )-bisindole-2-ones using o -bromophenylacetamide as sole starting material. The reaction mechanism is elucidated in light of the control experiment results. Graphical abstract: